The assassin [compact disc, unabridged] - Cussler, Clive (Cussler, Clive. Isaac Bell novels, 2015)
As Van Dorn private detective Isaac Bell strives to land a government contract to investigate John D. Rockefeller's Standard Oil monopoly, the case takes a deadly turn. A sniper begins murdering opponents of Standard Oil, kills Bell's best witness, a brave and likable man. Then the shooter detonates a terrible explosion that sets the victim's independent refinery ablaze. Bell summons his best detectives to scour the site of the crime for evidence.